Circulating pro fibrotic protein promotes fibrosis in liver. (25th November 2020) - Hsiao, Y; Shimizu, I; Yoshida, Y; Ikegami, R; Hayashi, Y; Suda, M; Katsuumi, G; Wakasugi, T; Nakao, M; Minamino, T
Abstract: Background/Introduction: Non-alcoholic steatohepatitis (NASH), driven by the obesity epidemic, has become the most common form of liver disease. Inflamed visceral adipose tissue secretes pro-inflammatory adipokines that are causal for systemic metabolic disorders. Role of adipokines in NASH, especially those from brown adipose tissues (BATokine) remain unclear. Purpose: To show the pathogenic role of BATokine in NASH. Methods: To identify and characterize the pathological roles of pro-fibrotic BATokine, we generated a murine obese NASH model by imposing a high fat diet in C57BL6/NCr mice, and murine systemic or BAT specific knockout (KO) models. We also conducted functional in-vitro studies with differentiated brown adipocytes. Results: Analyzing two sets of DNA micro array data with bioinformatics, we identified a secreted form pro-fibrotic protein (sPFP) expressed in dysfunctional brown adipose tissues (BAT) in mice. Testing our biobank samples, we found this protein increased in plasma of NASH patients. We generated a murine obese NASH model by imposing a high fat diet in C57BL6/NCr mice for 9–10 months since 4 weeks of age, and found that sPFP is produced predominantly by BAT. In this model, we also found that sPFP increased in plasma. We generated a murine systemic or BAT specific sPFP knockout (KO) models and found that liver fibrosis ameliorated in these models. We also suppressed circulating sPFP with a peptide vaccine targeting this molecule, and found that sPFP vaccination therapy inhibited liver fibrosis. Next, we generated sPFP gain of function (GOF) model by the administration of plasmid encoding sPFP into skeletal muscle. Liver fibrosis augmented in sPFP-GOF model, and these results suggested that sPFP has causal role for the progression of fibrotic response in liver. In vitro studies with differentiated brown adipocytes showed that metabolic stress increased c-Fos in nuclear, and this was causal for an increase in sPFP level. Conclusions: Our results suggest that one of the BATokines, sPFP, contributes for the progression of fibrotic responses in obese-NASH model. Inhibition of sPFP may become a therapy for NASH or obesity related fibrotic disorders. Funding Acknowledgement: Type of funding source: None